Simple and fast spectrophotometric determination of H2O2 in photo-Fenton reactions using metavanadate - Nogueira, RFP; Oliveira, M. C.; Paterlini, W. C. (Elsevier B.V., 2005)
This work proposes a spectrophotometric method for the determination of hydrogen peroxide during photodegradation reactions. The method is based on the reaction of H2O2 with amonium metavanadate in acidic medium, which results in the formation of a red-orange color peroxovanadium cation, with maximum absorbance at 450 nm. The method was optimized using the multivariate analysis providing the minimum concentration of vanadate (6.2 mmol L-1) for the maximum absorbance signal. Under these conditions, the detection limit is 143 mu mol L-1. The reaction product showed to be very stable for samples of peroxide concentrations up to 3 mmol L-1 at room temperature during 180 h. For higher concentrations however, samples must be kept refrigerated (4 degrees C) or diluted. The method showed no interference of Cl- (0.2-1.3 mmol L-1), NO3- (0.3-1.0 mmol L-1), Fe3+, (0.2-1.2 mmol L-1) and 2,4-dichlorophenol (DCP) (0.2-1.0 mmol L-1). When compared to iodometric titration, the vanadate method showed a good agreament. The method was applied for the evaluation of peroxide consumption during photo-Fenton degradation of 2,4-dichlorophenol using blacklight irradiation. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: hydrogen peroxide; vanadate; photo-Fenton; 2,4-dichlorophenol; spectrophotometry; degradation